Prevalence of Elevated Blood Lead Levels and Risk Factors Among Residents Younger Than 6 Years, Puerto Rico—2010. Issue 1 (January 2016) - Dignam, Timothy; García, Brenda Rivera; De León, Maridali; Curtis, Gerald; Creanga, Andreea A.; Azofeifa, Alejandro; O'Neill, Maureen; Blanton, Curtis; Kennedy, Chinaro; Rullán, Maria; Caldwell, Kathy; Rullán, John; et al.
Abstract : Context: Limited data exist about blood lead levels (BLLs) and potential exposures among children living in Puerto Rico. The Puerto Rico Department of Health has no formal blood lead surveillance program. Objectives: We assessed the prevalence of elevated BLLs (≥5 micrograms of lead per deciliter of blood), evaluated household environmental lead levels, and risk factors for BLL among children younger than 6 years of age living in Puerto Rico in 2010. Methods: We used a population-based, cross-sectional sampling strategy to enroll an island-representative sample of Puerto Rican children younger than 6 years. We estimated the island-wide weighted prevalence of elevated BLLs and conducted bivariable and multivariable linear regression analyses to ascertain risk factors for elevated BLLs. Results: The analytic data set included 355 households and 439 children younger than 6 years throughout Puerto Rico. The weighted geometric mean BLL of children younger than 6 years was 1.57 μg/dL (95% confidence interval [CI], 1.27-1.88). The weighted prevalence of children younger than 6 years with BLLs of 5 μg/dL or more was 3.18% (95% CI, 0.93-5.43) and for BLLs of 10 μg/dL or more was 0.50% (95% CI, 0-1.31). Higher mean BLLs were significantly associated with data collection during the summer months, a lead-related activity or hobby of anyone in the residence, and maternal education of less than 12 years. Few environmental lead hazards were identified. Conclusions: The prevalence of elevated BLLs among Puerto Rican children younger than 6 years is comparable with the most recent (2007-2010) US national estimate (BLLs ≥5 μg/dL = 2.6% [95% CI = 1.6-4.0]). Our findings suggest that targeted screening of specific higher-risk groups of children younger than 6 years can replace island-wide or insurance-specific policies of mandatory blood lead testing in Puerto Rico. Abstract : This article describes prevalence of elevated blood lead levels and risk factors among children younger than 6 years in Puerto Rico in 2010.